Study of Liquid Film Flow Structure on Inclined Wall Using Photochromic Dye Marking Method - Nurrina, Rosli; Amagai, Kenji (Japanese Society for Experimental Mechanics (JSEM), 2015)
The purpose of this study is to experimentally investigate the flow structure of liquid film flowing down an inclined wall using photochromic dye marking method. The dye trace was marked by UV laser (λ= 355nm) and its behavior was recorded by a CCD camera to obtain the liquid film surface velocity. The diameter change of the dye trace was measured with the velocity. The velocity was then compared to the diameter change of the dye trace to clarify the flow structure during the presence of wave. As a result, the liquid film surface velocity was found to decrease in the wave front and rapidly increase in the wave back.